The role of antibiotic-mercury interactions in wetlands: a review of methylation processes and ecological implications - Dong, Kun; Yang, JiaYu; Du, Chao; Ge, Conghao; Liao, Chenchen; Hui, Fujiang; Wang, Dunqiu; Yao, Yi (Frontiers in Environmental Science, 2026)
Antibiotics and Hg, as common environmental contaminants, are prevalent in different environmental media, including water and soil. Their collective pollution presents potential hazards to ecosystems and human health. This research comprehensively examines the present state of antibiotic-Hg co-contamination and their interaction mechanisms. Studies demonstrate that their interactions are intricate, encompassing both chemical and biological dimensions. Antibiotic molecular structures, such as carboxyl and amino groups, can chemically create chelating compounds with Hg, influencing its adsorption-desorption dynamics and bioavailability. Specific antibiotics (e.g., methl-containing antibiotics) may provide methyl groups during breakdown, thus facilitating Hg methylation and producing highly toxic methylmercury (MeHg). Antibiotics biologically modify microbial community structures, consequently affecting the equilibrium between the biological methylation and demethylation of Hg. Moreover, antibiotic exposure may influence Hg metabolism in organisms and is linked to the co-selection of Hg resistance genes (MRGs) and antibiotic resistance genes (ARGs), hence exacerbating environmental concerns. The present comprehension of the mechanisms by which antibiotics influence Hg transport, transformation, and toxicity is contentious and inadequate, especially in specialized ecosystems such as wetlands. Consequently, a thorough examination of their interconnections is crucial to establish a scientific foundation for evaluating and managing combined pollution hazards.